2017
DOI: 10.4172/2167-0412.1000286
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Aroma-acupoint Therapy and Aromatherapy to Treat Depression in Dementia Patients with Severe Cognitive Impairment

Abstract: Background: Depression, one of the most common behavioral and psychological symptoms of dementia in seniors, adversely affects life quality of both patients and caregivers. Because many antipsychotic drugs can cause severe side effects in patients with dementia, there is a need for effective noninvasive treatments for depression in these patients. This study compared the effect of aroma-acupoint therapy and aromatherapy on depression in DSM-IV diagnosed senior dementia patients with Mini-Mental State Examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Sleepiness, nausea, skin irritation, gait instability, and falls were reported by those participants who received a topical application of lavender essential oil [79]. Ten studies [48, 67‒69, 71, 72, 75, 77, 78, 82, 83] reported negligible or no adverse events among the participants who received aromatherapy, and the remaining 9 studies [45, 65, 66, 70, 73, 74, 76, 81, 88] have not assessed the safety of aromatherapy on PWD.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Sleepiness, nausea, skin irritation, gait instability, and falls were reported by those participants who received a topical application of lavender essential oil [79]. Ten studies [48, 67‒69, 71, 72, 75, 77, 78, 82, 83] reported negligible or no adverse events among the participants who received aromatherapy, and the remaining 9 studies [45, 65, 66, 70, 73, 74, 76, 81, 88] have not assessed the safety of aromatherapy on PWD.…”
Section: Resultsmentioning
confidence: 99%
“…While 3 quantitative studies reported that aromatherapy may have adverse effects [47, 79, 80], 10 reported negligible or no adverse events [48, 67‒69, 71, 72, 75, 77, 78, 82, 83] after completing the aromatherapy program. However, these safety issues were not described in the qualitative studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations